Discursive constructions of literacies: shifting sands in Aotearoa New Zealand. Issue 2 (4th March 2017) - Sandretto, Susan; Tilson, Jane
ABSTRACT: Literacy policy and pedagogy in Aotearoa New Zealand have a strong discursive heritage of traditional literacies, which emphasise code breaking and meaning making with linguistic codes and conventions over other possible modes of communication. In a rapidly evolving landscape where changes in communication technologies give birth to new literacies that make use of all the codes we have available for design, we argue teachers need support to augment and (re)conceptualise their literacy conceptions and pedagogy. In this paper we draw on five years of literacy research in Aotearoa New Zealand that supported 34 primary and secondary teachers to critically examine their literacy practices. Foucauldian informed discourse analysis of interview transcripts identified slight shifts in literacy practices, overshadowed by a spectre of accountability that impeded large-scale shift. This work highlights the difficulty of supporting and sustaining change given the global landscape of policy discourses accentuating accountability.